Intervención de enfermería en la administración de medicamentos en pediatría - Mery Luz Valderrama Sanabria (Universidad Francisco de Paula Santander, 2018)
Introduction: The plan was to unite two care actions, medication administration along with applying the nursing process to evaluate a favorable answer in children with respiratory diseases. The objective was to explore the effect of a nursing intervention in the medication administration of children with respiratory diseases. Materials and methods: Pre-experimental study, with two groups, composed by 26 children in each case. Criteria of inclusion: children younger than 5 years old with a respiratory disease, hospital stay of at least two days, with a permanent caretaker of legal age. The sample was calculated for convenience and recollected from April through June of 2016. The measurement instrument built was validated by experts. Results: The experimental group had differences in terms of weight gains, hospital stay, parents' comprehension about learning the safe use of the medication, amongst other variables regarding children that did not receive intervention. Conclusions: The nursing process is useful in the academic formation giving identity to the professional exercise, the instrument facilitated the learning process of the nursing student amongst with the purpose to offer children a safe environment. With the intervention, the correct and safe administration of medication is promoted, and at the same time it contributes to the nursing practice based on evidence.